The Influence of Website Design Quality, Perceived Value, E-Trust and Mediating Effects on Satisfaction on Repurchase Intentions (Case Study: Tokopedia.Com) - Yulin, Martha; Bernarto, Innocentius (Institute of Computer Science (IOCS), 2024)
Indonesia is predicted to become the country with the largest economy in the future, has made Indonesia a target for the entry of many e-commerce companies, so that market conditions become very competitive which requires industry players to maintain consumer loyalty. The influence of Website design quality, perceived value and E-trust on Repurchase intention through E-satisfaction as mediation in the e-commerce industry. This research was conducted using a causal study approach on 403 research respondents who were consumers of Tokopedia, which is one of the largest e-commerce in Indonesia. The research results show that website design quality, perceived value and satisfaction have a significant and positive influence on repurchase intention. However, E-trust does not have a significant influence on repurchase intention